2006
DOI: 10.1007/s10964-006-9090-1
|View full text |Cite
|
Sign up to set email alerts
|

Music Taste Groups and Problem Behavior

Abstract: Internalizing and externalizing problems differ by musical tastes. A high school-based sample of 4159 adolescents, representative of Dutch youth aged 12 to 16, reported on their personal and social characteristics, music preferences and social-psychological functioning, measured with the Youth Self-Report (YSR). Cluster analysis on their music preferences revealed six taste groups: Middle-of-the-road (MOR) listeners, Urban fans, Exclusive Rock fans, Rock-Pop fans, Elitists, and Omnivores. A seventh group of mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
59
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(65 citation statements)
references
References 30 publications
2
59
0
4
Order By: Relevance
“…More specifically, from the 1980s onward, young people preferring rock genres, such as heavy metal, gothic, and punk, consistently showed more risky behaviors, such as drunk driving, speeding, alcohol and drug use, and minor delinquencies in Canadian, Dutch, US, and Swedish studies. 5,[28][29][30] In Canadian and Dutch studies, different types of hip-hop fans were more likely to be involved in gangs, minor delinquency, and alcohol and drug use. 5,30,31 In a rare 2-year longitudinal investigation, Selfhout and colleagues 32 reported that both heavy metal and hip-hop fans reported more externalizing problems.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, from the 1980s onward, young people preferring rock genres, such as heavy metal, gothic, and punk, consistently showed more risky behaviors, such as drunk driving, speeding, alcohol and drug use, and minor delinquencies in Canadian, Dutch, US, and Swedish studies. 5,[28][29][30] In Canadian and Dutch studies, different types of hip-hop fans were more likely to be involved in gangs, minor delinquency, and alcohol and drug use. 5,30,31 In a rare 2-year longitudinal investigation, Selfhout and colleagues 32 reported that both heavy metal and hip-hop fans reported more externalizing problems.…”
mentioning
confidence: 99%
“…1,2 Although public claims that engaging with "deviant" media will inevitably lead to problem behavior are wildly exaggerated, 3 social scientific research has uncovered associations between media use, particularly music listening and music video watching, and a range of externalizing problem behaviors, including minor delinquency. [4][5][6] Until now, the music-problem behavior link has never been studied from a developmental perspective spanning adolescence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Mulder et al (2007) discovered that rock fans among others exhibited more problem behaviour and thinking than fans of more mainstream music, the latter apparently offering a 'buffering' effect against problems. We found a conviction on the part of many authors (e. g. Schwartz and Fouts 2003) that somehow personality dimensions can be 'read off' from a young person's music tastes and that 'heavier' music tastes can be seen as indicative of developmental difficulties and personality problems.…”
mentioning
confidence: 99%
“…De fato, a preferência musical tem estado relacionada com alguns traços ou fatores da personalidade, quer em termos dos cinco grandes (Rawlings & Ciancarelli, 1997;Rentfrow & Gosling, 2003;Pimentel & Donnely, 2008) ou de outros modelos (Mccown, Keiser, Mulhearn, & Williamson, 1997;North, Desborough, & Skarstein, 2005;Pearson & Dollinger, 2004). têm revelado correlações significativas da preferência musical com orientação política (Fox & Williams, 1974), estilos de vida (North & Hargreaves, 2007), valores (Boer, 2009;Leming, 1987), autoestima (Rentfrow & Gosling, 2006), viés intergrupal (Bakagiannis & Tarrant, 2006), risco de suicídio (Lacourse, Claes, & Villeneuve, 2001), habilidades cognitivas (Rentfrow & Gosling, 2003), problemas familiares, uso de drogas, comportamento sexual de risco e condutas antissociais (Arnett, 1991;Dent et al, 1992;Mulder, Bogt, Raaijmakers, & Vollebergh, 2006;Singer, Levine, & Jou, 1993). No âmbito dos estudos nacionais, é possível encontrar pesquisas que relacionem a preferência musical com valores e identificação grupal (Pimentel, 2004), comportamentos e atitudes antissociais (Pimentel, Gouveia, & Vasconcelos, 2005) e com risco de suicídio (Pimentel, Gouveia, Lima, Chaves, & Rodrigues, 2009).…”
unclassified